Perlindungan Hukum Perawatan Paksa Orang Dengan Gangguan Jiwa - Praptono, Eddhie; Pratama, Erwin Aditya (Universitas Pancasakti Tegal, 2021)
Most treatments of people with mental disorders (ODGJ) are forced or involuntary care. Human rights ensure that persons with disabilities are entitled to enjoy independence based on equality with others. Deprivation of liberty is allowed only if it is lawful and is done without arbitrary. The criminal law has set a ban on the deprivation of independence if it meets all its elements. The study examined whether the forced treatment of people with mental disorders in Indonesia when analyzed, associated with deprivation of independence, is a violation of criminal law and human rights, and how harmonization with forced care regulations. The results of this study show that the deprivation of independence in forced care in health institutions does not meet the elements of unlawful acts because there are clear rules, while in non-health institutions there are no clear rules and there may be acts of deprivation of independence that need further research. Forced Care needs to be harmonized with the current Law, namely: Law No. 32 of 2009 concerning Health; Law No. 18 of 2014 on Mental Health; and Law No. 8 of 2016 concerning Persons with Disabilities.